The Application of the Thinking in Pairs-Sharing with the Class Learning Model in an Effort to Improve Student Learning in The Integrated IPS Subject of Private SMP Santa Theresia Lahewa - Wahyutra Adilman Telaumbanua (Universitas Muhammadiyah Enrekang, 2023)
This research aims: (1) To know the use of the Think-Pair-Share Learning Model with the Class in the teaching and learning process in Integrated Social Studies class VIII at St. Theresia Lahewa Private Junior High School. (2) To determine the learning outcomes of students in Integrated Social Studies subjects at Private Junior High School St. Theresia Lahewa by using the Think-Pair-Share Classroom Learning Model. There is also the formulation of the problem in this study are (1) how the application of the Think-Pair-Share learning model with the class on Integrated Social Studies subjects in class VIII at SMP Swasta St. Theresia Lahewa. (2) how the learning outcomes of students in Integrated Social Studies subjects in class VIII with the application of the Think-Pair-Share Learning Model with Class at Private Junior High School St. Theresia Lahewa. The variables studied include two things, namely the learning model of Think-Pair-Share with Class (B3K) as an independent variable (X) and learning outcomes as the dependent variable (Y). Based on the results that researchers found at the research location, it is known that (1) the average observation results for teachers in the implementation of cycle I was 45.13%. In the second cycle observation, it increased to an average of 88.88%. The increase between the first and second cycles illustrates that there is an increase in the teacher's ability to apply the Think-Pair-Share Learning Model with the Class. (2) Based on the observation results for student activities in cycle I the average reached 45.82% and in cycle II the average increased to 89.24%. The increase between cycle I and II illustrates that the level of student activeness in participating in the teaching and learning process by using the Think-Pair-Share Learning Model with the Class is increasing. Based on the research findings, discussion and conclusions in this study, some suggestions from researchers are (1) In the learning process, teachers should be able to apply the Think-Pair-Share Learning Model with the Class (2) Every teacher should never get tired of improving weaknesses in carrying out the learning process (3) Students are expected to be more enthusiastic and motivated in receiving lessons by following the steps of the Think-Pair-Share Learning Model with the class (4) The results of this study should be used as comparison material for other researchers.